Long-Term Effects of Nusinersen Combined Physiotherapy in Spinal Muscular Atrophy Type 1: A Case Study - Güllü Aydın Yağcıoğlu; Numan Bulut; Fatma Uğur; İpek Alemdaroğlu Gürbüz; A. Ayşe Karaduman; Öznur Yılmaz (Journal of Behçet Uz Children's Hospital, 2022)
Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder that is characterized by generalized muscle weakness. Any study does not exist showing the results of Nusinersen and physiotherapy in SMA type 1. Our case was diagnosed with SMA type 1 at the age of 3 months. At 8 months of age, Nusinersen treatment and physiotherapy were started. The motor skills were evaluated with CHOP-Intend and Hammersmith Infant Neurological Examinations-2 (HINE-2) before physiotherapy and Nusinersen treatments, and also applied before each dose of Nusinersen during 22 months. An increase of 14 and 13 points in CHOP-Intend and HINE-2 were shown from baseline to the last visit, respectively. This report revealed the improvement of motor functions of a child with SMA type 1 by the combination of physiotherapy and Nusinersen. Our study may encourage physiotherapists and physicians to long-term use of a combination of these two therapies for the aim of motor improvement in this neuromuscular disease.